2023
DOI: 10.1002/pon.6255
|View full text |Cite
|
Sign up to set email alerts
|

Fear of cancer recurrence in ovarian cancer caregivers: A qualitative study

Kyra Webb,
Louise Sharpe,
Hayley Russell
et al.

Abstract: AimAlthough there is growing research exploring survivor fear of cancer recurrence (FCR), little is known about caregiver FCR. To date, examination of caregiver FCR has largely been conducted through the lens of survivor conceptualisations, limiting the development of caregiver‐specific models, measures, and interventions. This study aimed to explore experiences of FCR among caregivers of people with ovarian cancer.MethodsSemi‐structured telephone interviews were conducted with caregivers of people with ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…13 These findings were supported by a second qualitative study, exploring ovarian cancer caregiver experiences specifically. 17 This study found caregivers expressed a need to protect the person, but also to engage in self-protection strategies. These protective strategies were used by caregivers to decrease the likelihood of experiencing distress associated with the fear of the survivor's cancer returning, such as minimising concerns.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…13 These findings were supported by a second qualitative study, exploring ovarian cancer caregiver experiences specifically. 17 This study found caregivers expressed a need to protect the person, but also to engage in self-protection strategies. These protective strategies were used by caregivers to decrease the likelihood of experiencing distress associated with the fear of the survivor's cancer returning, such as minimising concerns.…”
mentioning
confidence: 78%
“…A caregiver-specific FCR model explaining the relationship between themes was proposed (See Figure S1). 17 Fear and uncertainty were central to caregiver experiences, which resulted in attempts to exert control and a sense of personal responsibility. 13,17 Driving fear was the caregiver's role as protector, which was dual in nature: (i) to manage the caregiver's own worries and fears, and/or (ii) to protect the survivor from distress.…”
mentioning
confidence: 99%
See 3 more Smart Citations